Tinjauan Kebijakan Anti-Dumping Indonesia dalam Menghadapi Praktik Perdagangan Tidak Adil terhadap Negara Berkembang - Widyarini Ardyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines Indonesia’s anti-dumping policy as an effort to protect domestic industries from unfair trade practices that significantly harm developing countries. The issue analyzed concerns the effectiveness of the Indonesian Anti-Dumping Committee (KADI) in conducting investigations and enforcing policies in accordance with WTO regulations. The research employs a normative legal approach through an analysis of legislation and principles of international trade. The findings show that Indonesia possesses an adequate legal framework, yet its implementation remains limited due to coordination challenges, investigative capacity constraints, and pressure from developed countries that often use anti-dumping instruments as tools of protectionism. The study concludes that strengthening KADI’s role, ensuring transparency in investigations, and enhancing governmental support are necessary. It is recommended to improve industrial capacity, harmonize regulations, and reinforce trade diplomacy.